Hand's end : technology and the limits of nature - Rothenberg, David, 1962- (University of California Press, 1993)
"Hand's End offers a radical new look at technology as the fundamental way in which we experience and define nature - the tool as humanity extended. Through history, says David Rothenberg, our view of the natural world has changed continually according to the new ways society has invented to use it. Tools extend our presence in the world while reconfiguring nature according to human understanding. As we extend the hand in different ways, we perceive anew whatever we touch. It changes, and so do we."--BOOK JACKET. "According to this subtle and original theory, the natural world cannot be meaningfully opposed to human civilization. Instead, we need to consider how many meanings nature has had in various periods and see it as a changing reflection of our perceived role in the world. This new perspective has profound consequences for both philosophy and ecology, which Rothenberg proceeds to elucidate by examining human inventions from the water wheel to the nuclear bomb and considering the ultimate goal each seems poised to reach. The discussion builds on previous theories of technology, including those of Plato, Aristotle, Bacon, Spinoza, Marx, Heidegger, Mumford, and McLuhan."--BOOK JACKET. "Once we are aware of the limits of technology, Rothenberg argues, we need to temper technical innovation with ideals not generally associated with the development of machinery. We can use technique, not to oppose and master the natural world but to make it our home. This work is certain to provoke wide discussion among philosophers and cultural historians, as well as environmentalists, architects, engineers, futurists, planners, and all those concerned with how technology can find a place within the very nature it threatens to destroy."--Jacket.